UHRF1: The key regulator of epigenetics and molecular target for cancer therapeutics - Harsimran Sidhu; Neena Capalash (Tumor Biology)
UHRF1 is a master regulator of epigenome as it coordinates DNA methylation and histone modifications. Compelling evidence suggests a strong link between UHRF1 overexpression and tumorigenesis, substantiating its ability to act as a potential biomarker for cancer diagnosis and prognosis. UHRF1 also mediates repair of damaged DNA that makes cancer cells resistant toward cytocidal drugs. Hence, understanding the molecular mechanism of UHRF1 regulation would help in developing cancer therapeutics. Natural compounds have shown applicability to downregulate UHRF1 leading to growth arrest and apoptosis in cancer cells.